Description and validation of some European forest syntaxa – a supplement to the EuroVegChecklist - Willner, Wolfgang; Solomeshch, Ayzik; Čarni, Andraž; Bergmeier, Erwin; Ermakov, Nikolai; Mucina, Ladislav (Hacquetia, 2016)
In this paper we present nomenclatural adjustments and validations of syntaxa of the forest vegetation of Europe. We introduce a new, valid name of the class of nemoral coniferous or mixed forests (Asaro europaei-Abietetea sibiricae) replacing the deciduous Carpino-Fagetea in the easternmost Europe and Siberia. We describe two new orders for birch and birch-poplar woodlands, formerly included in the Betulo pendulae-Populetalia tremulae. We validate the names of two alliances for the deciduous forests of the Southern Urals and the name of an alliance for hemiboreal forest swamps. The suballiance Ostryo-Tilienion, coined to accommodate the xerothermophilous ravine forests of SE Europe, is here elevated to the rank of alliance. Finally, we validate the name Quercion alnifoliae (evergreen oak forests of Cyprus).